Donor derived hematopoietic stem cell niche transplantation facilitates mixed chimerism mediated donor specific tolerance - Zhang, Wensheng; Wang, Yong; Zhong, Fushun; Wang, Xinghuan; Sucher, Robert; Lin, Cheng-Hung; Brandacher, Gerald; Solari, Mario G.; Gorantla, Vijay S.; Zheng, Xin Xiao (Frontiers in Immunology, 2023)
Compelling experimental evidence confirms that the robustness and longevity of mixed chimerism (MC) relies on the persistence and availability of donor-derived hematopoietic stem cell (HSC) niches in recipients. Based on our prior work in rodent vascularized composite allotransplantation (VCA) models, we hypothesize that the vascularized bone components in VCA bearing donor HSC niches, thus may provide a unique biologic opportunity to facilitate stable MC and transplant tolerance. In this study, by utilizing a series of rodent VCA models we demonstrated that donor HSC niches in the vascularized bone facilitate persistent multilineage hematopoietic chimerism in transplant recipients and promote donor-specific tolerance without harsh myeloablation. In addition, the transplanted donor HSC niches in VCA facilitated the donor HSC niches seeding to the recipient bone marrow compartment and contributed to the maintenance and homeostasis of stable MC. Moreover, this study provided evidences that chimeric thymus plays a role in MC-mediated transplant tolerance through a mechanism of thymic central deletion. Mechanistic insights from our study could lead to the use of vascularized donor bone with pre-engrafted HSC niches as a safe, complementary strategy to induce robust and stable MC-mediated tolerance in VCA or organ transplantation recipients.